Association between coffee intake and the risk of oral cavity cancer: a meta-analysis of observational studies. Issue 1 (January 2020) - He, Tao; Guo, Xiangyu; Li, Xue; Liao, Chunjuan; Yin, Wei
Abstract : The association between coffee intake and the risk of oral cavity cancer has been inconsistent in previous studies. Therefore, we conducted a meta-analysis to summarize the evidence regarding the strength of association between coffee intake and oral cavity cancer. PubMed, Embase, and Cochrane Library were searched to select studies on the relationship between coffee intake and oral cavity cancer conducted up to September 2018. Case–control or cohort studies and those that have reported about the effect estimates with 95% confidence intervals (CIs) of oral cavity cancer according to the different categories of coffee intake were included. The odds ratio (OR) and its corresponding 95% CI were calculated using the random-effects model. Fourteen case–control and five cohort studies that recruited 6456 patients with oral cavity cancer were included in the final quantitative meta-analysis. High versus low coffee intake was associated with a reduced risk of oral cavity cancer (OR: 0.68; 95% CI: 0.56–0.82; P < 0.001) in case–control studies (OR: 0.70; 95% CI: 0.55–0.90; P = 0.006) and cohort studies (OR: 0.65; 95% CI: 0.48–0.87; P = 0.004). Moreover, intermediate coffee intake was significantly associated with a reduced risk of oral cavity cancer (OR: 0.85; 95% CI: 0.77–0.94; P = 0.002), and such associations were mainly observed in case–control studies (OR: 0.86; 95% CI: 0.76–0.98; P = 0.021) but not in cohort studies (OR: 0.83; 95% CI: 0.67–1.02; P = 0.071). High or intermediate coffee intake might have protective effects against oral cavity cancer. However, the underlying mechanisms must be further evaluated in large-scale prospective cohort studies. Abstract : Supplemental Digital Content is available in the text.